Answer:
A= 1
Step-by-step explanation:
Distribute
3
(
− 6
) = −
5
− 1 ( 7 + 3
)
3a - 18 = -5a - 1 ( 7 + 3a )
Rearrange terms
3
− 1
8 = −
5
−
1 ( 3
+ 7 )
3a - 18 = -5a - 3a - 7
Combine like terms
3
− 1
8 =
−5
− 3
− 7
3a - 18 = -8a - 7
Add 1
8 to both sides of the equation
3a - 18 = -8a - 7
3
− 1
8 + 1
8 = −
8
− 7 + 1
8
Simplify
<u>Add the numbers</u>
3
− 1
8 + 1
8 = −
8
− 7 + 1
8
3a = -8a - 7 + 18
<u>Add the numbers again
</u>
3
= −
8
−
7 + 1
8
3a = -8a + 11
Add 8
to both sides of the equation
3a = -8a + 11
3
+ 8
= −
8
+ 1
1 + 8
Simplify
<u>Combine like terms</u>
3
+ 8
= −
8
+ 1
1 + 8
1
1
= −
8
+ 1
1 + 8
<u>Combine like terms again</u>
1
1
= −
8
+ 1
1 + 8
11a = 11
Divide both sides of the equation by the same term
11a = 11
1
1
/
1
1 = 1
1 / 1
1
Simplify
<u>Cancel terms that are in both the numerator and denominator</u>
1
1
/
1
1 = 1
1 / 1
1
a = 11/11
<u>Divide the numbers</u>
a = 11/11
a = 1
<u />